2020
DOI: 10.1002/fsn3.1759
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of soy protein isolate powders containing soluble protein aggregates formed at varying pH

Abstract: Soy protein is widely used in food formulations, nutraceutical products, and beverages as an inexpensive functional and health-promoting ingredient (Wang, Liu, Ma, & Zhao, 2019). However, the protein solubility of soy protein often decreases during storage (Martins & Netto, 2006; Pinto, Lajolo, & Genovese, 2005). For example, soy protein isolate (SPI) solubility decreases by about 63% after 1-year storage at 42°C (Pinto et al., 2005). This insolubility of soy protein seriously affects its commercial applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…With the degree of glycosylation increasing, the protein thermal stability decreased, and the protein conformation partially expanded. 5,52,53 Some researchers suggested that the decrease of 4H d was related to protein aggregation, 55 which was consistent with the previous solubility studies in this study. The decrease in 4H d of 1:2-1.5 was the most significant, as was the decrease in solubility.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 91%
“…With the degree of glycosylation increasing, the protein thermal stability decreased, and the protein conformation partially expanded. 5,52,53 Some researchers suggested that the decrease of 4H d was related to protein aggregation, 55 which was consistent with the previous solubility studies in this study. The decrease in 4H d of 1:2-1.5 was the most significant, as was the decrease in solubility.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 91%
“…As displayed in Figure S13, the SEP/PEO films start being damaged at the corners from the first second of the complete immersion in different types of water and dissolve relatively slowly in acidic solutions at 10 s. This is probably because the pH of acidic solution is close to the isoelectric point of the protein, resulting in stronger interaction between proteins, which reduces the dissolution of the protein. 61 The degradation process of the three films completes in about 30 s. Also, the electrodes show no significant degradation after 72 h, which demonstrates their potential in supporting and protecting the films. The results indicate that the as-prepared nanofiber has good biodegradability, which reduces the burden of environmental pollution caused by electronic products to a certain extent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, the film completely degrades within 30 s. Besides, we have tested the degradation of SEP/PEO films in different types of water (NaCl solution, NaOH solution, and acetic acid solution). As displayed in Figure S13, the SEP/PEO films start being damaged at the corners from the first second of the complete immersion in different types of water and dissolve relatively slowly in acidic solutions at 10 s. This is probably because the pH of acidic solution is close to the isoelectric point of the protein, resulting in stronger interaction between proteins, which reduces the dissolution of the protein . The degradation process of the three films completes in about 30 s. Also, the electrodes show no significant degradation after 72 h, which demonstrates their potential in supporting and protecting the films.…”
Section: Resultsmentioning
confidence: 99%
“…The denaturation temperature of glycinin is higher (75.7 • C) compared to β-conglycinin (60.5 • C) at a 1% weight concentration. Conversely, β-conglycinin exhibits slower rates of aggregation and densification [105]. Thermal aggregation kinetics reveal that β-conglycinin has a slower rate of aggregation and densification, with monomers still observed at 100 • C, which eventually form soluble aggregates of limited size.…”
Section: Protein Subunits Importance and Overviewmentioning
confidence: 97%
“…Thermal aggregation kinetics reveal that β-conglycinin has a slower rate of aggregation and densification, with monomers still observed at 100 • C, which eventually form soluble aggregates of limited size. In contrast, the densification and nucleation processes of glycinin are quicker, resulting in insoluble aggregates with densified cores [105]. Thus, glycinin contributes to gel hardness, while β-conglycinin contributes to gel elasticity.…”
Section: Protein Subunits Importance and Overviewmentioning
confidence: 99%